Hybrid energy system: power generation from renewable sources for coastal areas in Bangladesh - Ahmed, Emad Uddin; Anushka, Mantaka Rawnaq; Islam, Md. Nahin; Biswas, Pritom (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.